Terminologization of coloronyms in French scientific chemical discourse: comprehensive analysis - M. V. Volkova (Дискурс профессиональной коммуникации, 2020)
Contemporary scientific discourse of chemistry is one of the fastest developing independent types of professional scientific communication. It is currently undergoing evolutionary transformation due to a number of extralinguistic factors. Terminologization of coloronyms (i.e. lexemes with the semantics of colour) contributes to never ending replenishment of the vocabulary of scientific-chemical communication. This paper is devoted to the study of current evolutionary trends concerning coloronyms in the French scientific-chemical discourse of the XXIst century. The author defines the notion of a coloronym and analyzes main transformations of colour terms in scientific-chemical discourse from the viewpoint of various linguistic aspects, e.g. etimology, semantics, morphological structure, syntax. The aim of the paper is to describe modern specificity of terminologization of coloronyms to further investigate evolutionary changes in French scientific-chemical discourse. Empirical material of the study comprises fragments of written discourse taken from specialized websites, connected with colour industry (factories “Le Moulin à Couleurs” and “Ressource Peintures”, antique evaluation office “Cabinet Portier et Associés”, dyestuff production company “Terres et Couleurs”). The author also uses illustrative examples including lexical units from scientific publications in chemistry that can be found in the digital archive “L’actualité chimique”. The study employs such methods as analysis of dictionary definitions, etymological, component, structural-semantic analyses. Based on the complex analysis of terminologization of coloronyms, the author singles out major tendencies in the development of colour terms in scientific-chemical discourse. Etymological analysis of coloronyms helps to follow all the steps in their semantic development in scientific-chemical communication. From the viewpoint of morphological structure, there are two diametrically opposite tendencies to simplification of the existing forms of coloronyms and at the same time to formation of new forms by making them more complex. As far as syntax is concerned, the author highlights the tendency to a wide variety of syntactical functions, performed by coloronyms.